Cytogenetic analysis of three species of Pseudacteon (Diptera, Phoridae) parasitoids of the fire ants using standard and molecular techniques - Chirino, M.G. (2009)
Pseudacteon flies, parasitoids of worker ants, are being intensively studied as potentially effective agents in the biological control of the invasive pest fire ant genus Solenopsis (Hymenoptera: Formicidae). This is the first attempt to describe the karyotype of P. curvatus Borgmeier, P. nocens Borgmeier and P. tricuspis Borgmeier. The three species possess 2n = 6; chromosomes I and II were metacentric in the three species, but chromosome pair III was subtelocentric in P. curvatus and P. tricuspis, and telocentric in P. nocens. All three species possess a C positive band in chromosome II, lack C positive heterochromatin on chromosome I, and are mostly differentiated with respect to chromosome III. P. curvatus and P. tricuspis possess a C positive band, but at different locations, whereas this band is absent in P. nocens. Heterochromatic bands are neither AT nor GC rich as revealed by fluorescent banding. In situ hybridization with an 18S rDNA probe revealed a signal on chromosome II in a similar location to the C positive band in the three species. The apparent lack of morphologically distinct sex chromosomes is consistent with proposals of environmental sex determination in the genus. Small differences detected in chromosome length and morphology suggests that chromosomes have been highly conserved during the evolutionary radiation of Pseudacteon. Possible mechanisms of karyotype evolution in the three species are suggested. Copyright © 2009, Sociedade Brasileira de Genética.